2007
DOI: 10.1021/es070832y
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Induced Spent Nuclear Fuel Dissolution under Deep Repository Conditions

Abstract: The dynamics of spent nuclear fuel dissolution in groundwater is an important part of the safety assessment of a deep geological repository for high level nuclear waste. In this paperwe discussthe most important elementary processes and parameters involved in radiation induced oxidative dissolution of spent nuclear fuel. Based on these processes, we also present a new approach for simulation of spent nuclear fuel dissolution under deep repository conditions. This approach accounts for the effects of fuel age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 22 publications
2
75
0
1
Order By: Relevance
“…The only question is how long it takes before a steady-state concentration of H 2 O 2 , is reached. This problem has been addressed in some previous papers where the system was simulated taking the geometrical dose distribution, the radiolytic production of H 2 O 2 , the surface reaction consuming H 2 O 2 and diffusion of H 2 O 2 into account [65,73,74]. Interestingly, the results of the simulations showed that the surface concentration of H 2 O 2 approaches the steady-state level within a matter of seconds to minutes, even though the bulk concentration is much lower.…”
Section: Influence Of Groundwater Componentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The only question is how long it takes before a steady-state concentration of H 2 O 2 , is reached. This problem has been addressed in some previous papers where the system was simulated taking the geometrical dose distribution, the radiolytic production of H 2 O 2 , the surface reaction consuming H 2 O 2 and diffusion of H 2 O 2 into account [65,73,74]. Interestingly, the results of the simulations showed that the surface concentration of H 2 O 2 approaches the steady-state level within a matter of seconds to minutes, even though the bulk concentration is much lower.…”
Section: Influence Of Groundwater Componentsmentioning
confidence: 99%
“…There are numerous other constituents that could also influence the process of radiation-induced oxidative dissolution [65][66][67]. A few of these constituents will be discussed here.…”
Section: Influence Of Groundwater Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…where _ DðxÞ is the dose rate at distance x from the fuel surface, q is the density of water and GðH 2 O 2 Þ is the radiation chemical yield for H 2 O 2 [31]. The maximum rate of the reaction between H 2 O 2 and the UO 2 surface corresponds to the steadystate.…”
Section: Dissolution Of Spent Nuclear Fuelmentioning
confidence: 99%